English articles and their translation into Czech - Hrůzová, Ivana (2006)
Annotation The thesis examines various aspects of the use of articles in English, especially their function in FSP and maps the means of translating them into Czech. The first part investigates the concept of definiteness first in general and later in particular dealing with English articles as the prototypical means of expressing definiteness and indefiniteness in English. The final chapter of the first part is devoted to the theory of functional sentence perspective considerig also the function of English articles with respect to functional sentence perspective. The second part is based on a comparative analysis of parallel English and Czech texts included in the corpus Kačenka/K2. It explores to what extent articles in English contribute to the distribution of communicative dynamism over the elements within a sentence and how it is reflected in the parallel Czech text